KAJIAN ETNOGRAFIS TENTANG MESBAH SEBAGAI SIMBOL IDENTITIAS SPRITUAL MASYARAKAT DESA KOPIDIL SUKU KABOLA - Halena Makunbok; Seli Djaha, Hana Klaudia Lammakoli, Harun Letmani, Hasanudin Leki, Halena Muna Bekata, Petrus Mau Te (Adiba Aisha Amira, 2025)
The purpose of this research is to present an ethnographic study of mesba as a symbol of the spiritual identity of the Kopodi Village community in Kabola sub-district. Research data analysis using qualitative descriptive analysis. The data used in the research is qualitative data. The data collection technique was carried out in two ways, namely field observation and interviews. This research was conducted in Kopidil Village, Kabola Sub- district, Alor Regency. The information in this research is traditional leaders. The results of this study indicate that: (1) Mesbah is one very important aspect in performing lego- lego dance. (2) lego-lego dance, kabola tribe, has similarities that are not much different from the tribes in alor district because it has similarities such as circular movements, hand in hand, and foot stomping. (3) traditional houses made of three warehouses and named Bangtowo means three large villages that temporarily hold activities in that place. (4) accompaniment musical instruments that are often used by the Kabola Tribe Community at lego-lego gong and drum performances (5) the traditional dress of the kabola tribe is a dress made of bark. However, in this study, researchers focused more on researching ethnographic studies of mesba as a symbol of the spiritual identity of the Kopidil village community, this research can be concluded that the Kopidil village community has an interesting Mesba story.